PG119 Adapting on-call simulation for final year medical students to an online format during the Covid-19 pandemic. (10th November 2020) - Stone, Stephanie; Stark, David; Bullock, Cameron
Abstract : Background: In 2019, a survey of Exeter final year medical students revealed they felt under-prepared for on-call work. To improve their knowledge, confidence 1 and on-call skills 2 we provided an in-situ on-call simulation in 2019. The feedback from students was overwhelmingly positive and, as a result, the simulation was due to be incorporated into the Exeter 2020 curriculum. Due to the COVID-19 pandemic, placements were cancelled resulting in heightened anxiety amongst final year students. We amended our teaching and designed a simulation to be provided using online platforms, aimed at improving final year student's confidence in on-call skills. Summary of Work: The scheme commenced with an online lecture, followed by small group virtual simulation sessions run by junior doctors. There was a short briefing on prioritisation, escalation and handover skills. Students were then 'bleeped' at regular intervals by the doctors who acted as ward-based staff. The students could choose in which order to complete these tasks and were sent relevant information, including ward notes and investigations. The session concluded with a 30 minute debrief. Summary of Results: 17 junior doctors and 17 students participated on a voluntary basis. Surveys before and after measured the schemes efficacy with answers ranked 1–100 (table 1 ). All students found the session useful and would recommend it to colleagues. Free text feedback praised the realistic scenarios, the benefit of independent working, the success of an online format and the value of time with junior doctors. All doctors enjoyed the session and felt it offered a valuable opportunity to develop teaching skills. Discussion and conclusions: This simulation increased the confidence of final year students approaching their first on-call. Online simulation provided a realistic experience without compromising student or patient safety during the Covid-19 pandemic. Although we hope to return to in-situ simulation, we feel this online format provides a good alternative if necessary. Recommendations: Online simulation provided a good substitute for in-situ training when limited by the Covid-19 pandemic. It would be useful to consider how other teaching can be adapted to ensure a consistent and high standard of medical education despite the impact of external factors. References: Okuda Y, Bryson EO, DeMaria S, Jacobson L, Quinones J, Shen B and Levine AI. The utility of simulation in medical education: what is the evidence? Mt Sinai J Med 2009;76:330–343. Berry M, Burrell F, Chapman RL, Gough S, Ewings S and Thackray D. Simulation-based training can improve on-call physiotherapists' clinical reasoning abilities and self-reported competency. Physiotherapy ( 2016);102:e269 – e270.